Whale-watching in Juneau, AK: Assessing Potential Effects on Humpback Whales and Understanding Passenger Perceptions - Schuler, Alicia Rinaldi (University of Alaska Fairbanks, 2019)
The feeding grounds of the North Pacific humpback whale (Megaptera novaeangliae) in Juneau, Alaska have rapidly developed into a popular whale watch destination during the summer (May-September). The whale watch industry has tripled in size in the last 18 years, currently numbering approximately 65 vessels. The sustainability of this industry could be jeopardized if the health and dependability of the resource, the whales, is negatively affected by increasing vessel pressure. The aim of this project is to provide a holistic understanding of whale watch tourism in Juneau by assessing 1) humpback whale responses to whale-watching vessels and 2) passenger experiences as a conduit for conservation of whales and the environment. Data were obtained during 2016 and 2017, comprising observations of 201 humpback whale groups and collection of 2331 passenger surveys. To address the first objective, shore-based measurements and observations of humpback whales were conducted to assess potential impacts of whale-watching vessels on short-term movement and behavioral patterns of whales. Linear mixed effects models indicated that the presence (vs. absence) of vessels was related to significantly higher deviation in linear movement, increased swimming speed, and shorter inter-breath intervals (IBI). For each additional vessel present, deviation increased and IBI significantly decreased. Linear regression models also indicated that as time spent in the presence of vessels increased, respiration rate (breaths per minute) increased. Markov chain analyses indicated that feeding and traveling humpback whales were likely to maintain their behavioral state regardless of vessel presence, while surface active humpback whales were likely to transition to traveling in the presence of vessels. To address the second objective, surveys were administered to passengers before, immediately after, and six months after a whale-watching tour to measure knowledge, intentions, behaviors, and attitudes over time. Following a whale-watching tour, awareness of whale-watching guidelines/regulations doubled and support for guidelines/regulations significantly increased and remained high six months later. Binomial logistic regression models determined that strong support for guidelines/regulations was more likely if participants were aware of guidelines/regulations and less likely if participants disagreed that vessels have a negative impact on whales. Lastly, linear regression models revealed that participants that acknowledged human impacts on whales and their habitat had stronger pro-environmental attitudes. As vessel presence increases in this region, adherence to whale watching guidelines/regulations is likely to become increasingly important to mitigate cumulative effects that may arise from short-term changes in whale behavior in a changing environment. It is recommended that management revisit the current measures in place to better suit the industry today, and that education during whale watching tours be included as a potential management tool to encourage operator compliance. The results presented in this thesis indicate that both management and the industry itself can help to develop a mutually beneficial industry for the whale watching operators, the whales, and the people that come to watch them.